Subsistence fishing patterns near food deserts - Savannah H. Swinea; Hailey Smith; Jonathan H. Grabowski; Sean P. Powers; Sara Wylie; Steven B. Scyphers (Proceedings of the National Academy of Sciences, 2025)
Fisheries are critical for sustaining waterfront communities. However, subsistence fishing is not well understood in the United States, despite its potential contributions to health and culture. We piloted a multivariable construct to classify subsistence vs. nonsubsistence fishers, identified the strongest predictor of participating in this practice, and tested for differences in place-based fishing motivations, behaviors, and community sharing. Among shore-based fishers in coastal Alabama, lower household income was the most powerful predictor of subsistence fishing. Subsistence fishers held more fishing motivations, targeted more specific fish groups, were more efficient in catching and keeping fish, and more frequently shared fish across social groups. Informed by these findings, we discussed management strategies to addressopportunities and barriers for shore-based subsistence fishing in coastal Alabama. More broadly, the framework piloted here offers a pathway to integrate subsistence fisheries into management using place-based evidence.